Implementation of Ethnomathematics in Mathematics Learning Videos for First Grade of Elementary School - Yandani, Putu Evi; Agustika, Gusti Ngurah Sastra (Universitas Pendidikan Ganesha, 2022)
Learning media used to support the learning process during the Covid-19 pandemic for grade I elementary school students is still unavailable, resulting in the learning process and students' understanding of learning, especially the content of mathematics material, is not optimal. The better the learning media, the better the student's competence. This study aims to create and determine the feasibility of ethnomathematics-based mathematics learning video media on the content of the solid geometry material. This study used the ADDIE development model using data collection methods: questionnaire, observation, and unstructured interviews. The method of data analysis used is descriptive qualitative and descriptive quantitative. The subjects of this research are material experts, design experts, and learning media experts, and the test subjects are first-grade elementary school students. Development research results are product design for ethnomathematics-based mathematics learning media and the feasibility of instructional video media. Mathematics based on the results of the assessment of learning material expert (93.75%), learning design expert (100%), learning media expert (95%), individual trial (92.36%), and a small group trial (93.05%). So, the ethnomathematics-based mathematics learning video introducing geometry material for first-grade elementary school students is feasible to use and can improve student competence. This research implies that students can learn mathematics using learning videos independently, meaningfully, and fun, and motivate teachers to develop various learning media.